The Grammatical Meaning of Prefix Basi- in Minangkabau - Irhamni, Mutia; Nasution, Khairina; Deliana; Widayati, Dwi (HM Publisher, 2024)
Prefix basi- functions grammatically and semantically based on the specific instance it is used. The concept of prefixes pertains to how prefixes have varying meanings based on their grammatical function and context. This study aims to analyze the grammatical functions used by Minangkabau speakers through the advanced analysis method. This method involves word class testing through synonym search, testing verb functions in sentences with continuous events, and testing nouns for acceptability as subjects, objects, and complements. The objective of this study is to provide an objective analysis of Minangkabau speakers' grammar, using clear and concise language, and following conventional academic structures while adhering to grammatical correctness and balanced language with the method of qualitative research by observing the speaker. The findings reveal that the prefix basi- possesses grammatical functions such as 1) indicating ongoing events, 2) expressing excessive actions or speech through expressions or phrases, 3) indicating the present condition and health of a person, 4) functioning as a causative and imperative, and 5) functioning as an adverb and 6) functioning as a noun.